Cross – Border Identity and Cultural Hybridity among Border Communities in Jayapura – Vanimo Borderline - Ongom, Trevor Graham; Ningrum, Etik Siswati; Handayani, Tri; Lodo, Ratzinger (Papua Journal of Diplomacy and International Relations, 2026)
This study examines how cultural interaction along the Jayapura–Vanimo frontier shapes cross-border identity and produces cultural hybridity. Using a qualitative, literature-based design, the research integrates border process theory, hybridity theory and Melanesian relational perspectives to interpret how everyday practices contribute to identity formation in this borderland. The analysis finds that mobility, reciprocal exchange, ritual participation, and kinship obligations create a relational environment that operates independently of the political boundary, demonstrating that identity is sustained through ongoing social interaction rather than administrative categorization. The study also finds that hybridity forms an organized configuration comprising ritual reciprocity, institutional blending, and expressive practices that enable residents to navigate both customary and state systems. This research contributes by demonstrating that relational obligation functions as the key mechanism linking cross border interaction in the Melanesian context to the resilience of hybrid identity, clarifying why cultural ties endure even in the face of policy shifts or mobility constraints. KEYWORDS Border Bnteraction; Cultural Hybridity; Identity Formation; Jayapura–Vanimo; Relational obligation